Impact of Zn-doping on the composition, stability, luminescence properties of silica coated all-inorganic cesium lead bromide nanocrystals and their biocompatibility. (March 2022) - Kar, M.R.; Chakraborty, R.; Patel, U.; Chakraborty, R.; Ray, S.; Acharya, T.K.; Goswami, C.; Bhaumik, S.
Abstract: Cesium lead halide (CsPbX3 : X = I, Br, Cl) nanocrystals (NCs) are believed to be potential candidates for bioimaging applications. However, their low structural stability against polar solvents remains as a major limitation. To improve the NCs stability and maintain high emission intensity, we synthesized silica coated Zn-doped core@shell perovskite NCs via modified ligand assisted reprecipitation (LARP) synthetic method under relatively high humid condition. We systemically varied the composition inside the perovskite structure and then studied their photophysical properties and stability. Interestingly, the Zn-doping amount controls the ratio of CsPbBr3 to Cs4 PbBr6 perovskites inside the core and also facilitates the growth of (OA)2 PbBr4 shell, enables overall increase in NCs emission intensity and stability. We observed green color emission from these NCs in the spectral range of 494-506 nm with a maximum photoluminescence quantum yield (PLQY) up to 88%. The optimized Zn-doped NCs exhibited nearly four times better water stability compared to the bare NCs and retain emission properties for several months even in highly polar solvents. Finally, we performed biocompatibility test of the NCs generated on biological samples and hydroponics test in a gardenia leaf for their potential bioimaging applications. Highlights: Silica-coated Zn-doped CsPbBr3 nanocrystals (NCs) are synthesized via ligand-assisted reprecipitation method. Zn-doping inside the perovskite structure controls the ratio of CsPbBr3 to Cs4 PbBr6 perovskites. Zn-doped NCs exhibit higher photoluminescence intensity and excellent water stability. These NCs showed emission spectra in the range of 494–506 nm with a maximum photoluminescence quantum yield of 88%. Potential use of these NCs for bioimaging applications.